REHABILITATION EFFECT OF CORRECTION OF ERECTILE DYSFUNCTION IN PATIENTS WHO UNDERWENT RADICAL PROSTATECTOMY FOR PROSTATE CANCER - A. T. Asratov; I. V. Vinogradov; B. R. Gvasaliya; A. A. Kachmazov; A. G. Kochetov; Yu. V. Samsonov; N. V. Sitnikov; A. O. Tolkachev; A. A. Kostin (Исследования и практика в медицине)
Purpose. To investigate the effect of the development of erectile dysfunction (ED) in patients with prostate cancer after radical prostatectomy (RPE) on the assessment of these patients’ quality of life and their psychological state and the influence on these parameters of ED treatment by implantation of the prosthesis of the penis.Materials and methods. The material of the study was analysis of the questionnaire data of 30 patients with PC with the postoperative ED before the postoperative period and after the falloprosthesis. In the long-term postoperative period (2–3 years) patients (n = 30) with an ED stand, who wanted to restore sexual function, were installed a 3-component prosthesis of the penis. The comparison group consisted of 38 patients, examined 3 years after RPE. The second comparison group consisted of 28 patients who were examined prior to surgical treatment. The questioning of patients was carried out using the questionnaire MIEF-5, which characterizes the state of sexual function, and the psychological test of Spielberger-Khanin for assessing anxiety.Results. Itwasshownthatthesumofthepointsofsituationalanxietyafterprostheticsofthepenisdecreasedfrom 32.4 ± 3.6 to 17.4 ± 1.5 points (p = 3.74-5), and personal anxiety – from 43.7 ± 2.2 to 33.0 ± 1.2 points (p = 1.71-5); and, these differences are statistically highly reliable. Accordingly, the evaluation of sexual function shifted in a positive direction (all patients confirmed satisfaction with the restored sexual function).Сonclusion. The results attest to the high rehabilitation efficiency of correction of ED, which developed after RP, by installing a falloprosthesis.